The Relationship between Self-Esteem and Sexual Risk-Taking Behaviours among Adolescent Students in Tanzania - Marandu, Daniel Fedrick; Mauki, Chris Mungubariki (Papers in Education and Development, 2023)
This paper quantitatively assessed the relationship between self-esteem and sexual risk-taking behaviours among adolescents. The study employed a correlation design, using a questionnaire for data collection. A total of 511 students participated in this study. The data was analysed using Pearson ' s Correlation Coefficient. Results showed no significant relationship between self-esteem and sexual debut (r =.081, p > 0.05), self-esteem and safe sex (r =.081, p > 0.05) and a weak positive relationship between self-esteem and multiple partners (r =.033, p .470). This implies that self-esteem did not influence sexual risk-taking behaviours. The study recommends for a related study using a qualitative approach to explore the role of other socio-cultural aspects that can influence adolescents to be involved in sexual risk-taking behaviours. Keywords: adolescents, multiple partners, safe sex, sex debut